Analysis of Aromatic Hydrocarbons in Oil and Gas Geochemical Exploration Samples by Fluorescence Spectrometry - LI Qing-xia; LIU Ya-xuan; CHEN Wei-ming; LIU Bin; ZHANG Qin (Yankuang ceshi, 2014)
Fluorescence spectrometry, with the characteristics of high sensitivity, low detection limits and rapid analysis, avoids complex separating work in the chromatography method, and is suitable for oil and gas geochemical exploration samples requiring a large number of assays. In this paper, sample pretreatment methods and analytical conditions that were optimized in order to analyse aromatic hydrocarbons in oil samples by fluorescence spectrometry are reported. Ultra pesticide residue grade n-hexane was selected as the extraction solvent, which simplified the purification operation, and intermittent oscillation was selected to improve the extraction effect of aromatics. Through selecting proper standard materials (naphthalene, phenanthrene and chrysene) and adopting an external standard method, aromatic hydrocarbon in the samples was determined under the optimal analytical conditions. With the excitation wavelength of 265 nm and the emission wavelength of 320 nm, 360 nm and 405 nm, the fluorescent spectra of aromatic hydrocarbon were studied. The relative intensities were converted into the concentration of a certain standard material, which could then be used to compare the fluorescence data between different laboratories and different instruments. The detection limit of the method was 1.8 ng/g (naphthalene), which was lower than the limit of the national industry standard (2.0 ng/g, SY/T 6009.8—2003). The precision results of the method (RSD, n=12) were 4.5% (320 nm), 9.6% (360 nm) and 14.7% (405 nm), respectively. Through improving the quality control and management, the proposed method has been conducted successfully in the Daqin oil field, and it was found that the fluorescent data could effectively indicate sampling depth and anomalies.